Combined oven/freeze drying as a cost and energy-efficient drying method for preserving quality attributes and volatile compounds of carrot slices - Mina, Zobabalo Progress; Kaseke, Tafadzwa; Fadiji, Tobi; Silue, Yardjouma; Fawole, Olaniyi Amos (Frontiers in Horticulture, 2025)
IntroductionAn effective and efficient drying method for preserving fresh carrots is essential in food processing. Combined drying represents a novel approach that addresses the shortcomings of conventional methods by balancing energy consumption, cost, and product quality.MethodsThis study evaluated the impact of combining oven drying (OD) with freeze-drying (FD) on drying behavior, energy requirements, costs, enzyme activity, and the physicochemical and sensory properties of dried carrots. Drying conditions included 36 hours of FD, OD, and combinations of OD and FD at 1 h of OD + 21 h of FD (OD1-FD21), 2 h of OD + 18 h of FD (OD2-FD18), 3 h of OD + 15 h of FD (OD3-FD15), and 9 h of OD.Results and discussionCompared to FD alone, the OD-FD combination reduced drying time by 39–50% and decreased energy consumption and costs by 40–56%. FD and OD-FD reduced polyphenol oxidase activity by 71–85% and peroxidase activity by 29–52% compared to OD alone. FD carrot slices retained significantly higher levels of β-carotene (11.67–25.96 mg/100 g DM), lycopene (9.91–21.85 mg/100 g DM), total phenolic content (7.12–10.24 mg GAE/100 g DM), and DPPH radical scavenging activity (16.44–19.38 mM AAE/100 g DM) than OD and OD-FD slices. OD-FD slices exhibited the highest levels of volatile compounds, including aldehydes, terpenes, esters, alcohols, ketones, and acids, indicating superior flavor preservation.ConclusionThe OD2-FD18 combination emerged as the optimal method, significantly reducing energy consumption and costs while maintaining better β-carotene, total phenolic content, DPPH radical scavenging activity, and volatile compound profiles. This study highlights the potential of combined drying methods to enhance drying efficiency and product quality.